Relationship between clonal hematopoiesis of indeterminate potential and severity of coronary stenosis in coronary heart disease patients with renal insufficiency - ZHONG Jialin; ZHONG Jialin; XIAO Ruonan; XIANG Shuting (陆军军医大学学报)
Objective To investigate the association between clonal hematopoiesis of indeterminate potential (CHIP) and the severity of coronary artery lesions in coronary heart disease (CHD) patients with renal insufficiency. Methods A case-control trial was conducted on 70 CHD patients with renal insufficiency admitted in Chongqing Emergency Medical Center (Affiliated Central Hospital of Chongqing University) and Department of Cardiovascular Diseases of the First Affiliated Hospital of Chongqing Medical University from December 2023 to July 2024.According to the median Gensini score, they were classified into the Gensini score < 44 group (n=34) and ≥44 group (n=36), and based on carrying CHIP mutation or not, they were divided into CHIP group (n=23) and non-CHIP group (n=47).The differences in clinical data were compared between the above 2 pair groups respectively.Binary logistic regression analysis was used to assess the relationship between CHIP status and the severity of coronary artery lesions. Results Compared with the Gensini score < 44 group, the Gensini score ≥44 group had a higher CHIP carriage rate (17.2%vs 47.6%, P=0.008) as well as NT-proBNP level (767 vs 3 480 ng/L, P=0.039).Binary logistic regression analysis showed that CHIP status was still associated with higher Gensini scores after adjustment of NT-proBNP (OR=3.935, 95%CI=1.153~13.435, P=0.029).Further CHIP grouping results suggested that the patients in the CHIP group had higher Gensini score (48 vs 38, P=0.004), larger proportion of 3-vessle disease (52.2%vs 25.5%, P=0.040), and lower left ventricular ejection fraction (55.0%vs 58.0%, P=0.042) than those in the non-CHIP group. Conclusion CHIP is an independent risk factor for severe coronary artery disease in CHD patients with renal insufficiency.